Nondestructive biomarkers of exposure to disrupting chemicals in endangered species endocrine of wildlife - FOSSI, M. C.; CASINI, S.; MARSILI, L. (Chemosphere, 1999)
This paper explores the problem of endocrine disrupting chemicals (EDCs) from the ecotoxicological point of view, focusing on nondestructive biomarkers of exposure to EDCs for risk assessment of endangered species of wildlife. Several EDCs, such as polyhalogenated aromatic hydrocarbons and toxic metals, tend to be biomagnified in the terrestrial and particularly the marine food chains. Top predators tend to accumulate high concentrations of these contaminants which places them in a situation of high toxicological risk. Hence, there is a need to develop nondestructive techniques, such as nondestructive biomarkers, for hazard assessment, protection, and conservation of endangered species exposed to EDCs. The biological materials proposed for this approach (for example blood, faeces, fur, skin biopsy specimens) are easily obtained with minimal stress for individuals and populations. Some validation data are reported on porphyrins in sea bird excreta (Lants dominicanus, Phalacrocorax olivaceus, Pelecanus occidentalis thagus), as nondestructive biomarkers of exposure to organochlorines, and on benzopyrene monooxygenase activities in marine mammal skin biopsy specimens (Stenella coeruleoalba, Balaenoptera physalus), as early indicators of exposure to p,p'-DDE and other endocrine disrupting organochlorines.